The response of the vestibulosympathetic reflex to linear acceleration in the rat - Yakushin, S. B. (J Neurophysiol, 2016)
The vestibulosympathetic reflex (VSR) increases blood pressure (BP) upon arising to maintain blood flow to the brain. The optimal directions of VSR activation and whether changes in heart rate (HR) are associated with changes in BP are still not clear. We used manually activated pulses and oscillatory linear accelerations of 0.2–2.5 g along the naso-occipital, interaural, and dorsoventral axes in isoflurane-anesthetized, male Long-Evans rats. BP and HR were recorded with an intra-aortic sensor and acceleration with a three-dimensional accelerometer. Linear regressions of BP changes in accelerations along the upward, downward, and forward axes had slopes of ≈3–6 mmHg · g(−1) (P < 0.05). Lateral and backward accelerations did not produce consistent changes in BP. Thus upward, downward, and forward translations were the directions that significantly altered BP. HR was unaffected by these translations. The VSR sensitivity to oscillatory forward-backward translations was ≈6–10 mmHg · g(−1) at frequencies of ≈0.1 Hz (0.2 g), decreasing to zero at frequencies above 2 Hz (1.8 g). Upward, 70° tilts of an alert rat increased BP by 9 mmHg · g(−1) without changes in HR, indicating that anesthesia had not reduced the VSR sensitivity. The similarity in BP induced in alert and anesthetized rats indicates that the VSR is relatively insensitive to levels of alertness and that the VSR is likely to cause changes in BP through modification of peripheral vascular resistance. Thus the VSR, which is directed toward the cardiovascular system, is in contrast to the responses in the alert state that can produce sweating, alterations in BP and HR, and motion sickness.